Silencing NUDT21 Attenuates the Mesenchymal Identity of Glioblastoma Cells via the NF-κB Pathway - Lou, Jia-Cheng; Lan, Yu-Long; Gao, Jin-Xia; Ma, Bin-Bin; Yang, Ting; Yuan, Zhong-Bo; Zhang, Hong-Qiang; Zhu, Ting-Zhun; Pan, Ning; Leng, Song; Song, Gui-Jun; Zhang, Bo (Frontiers in Molecular Neuroscience, 2017)
The proneural (PN) and mesenchymal (MES) subtypes of glioblastoma multiforme (GBM) are robust and generally consistent with classification schemes. GBMs in the MES subclass are predominantly primary tumors that, compared to PN tumors, exhibit a worse prognosis; thus, understanding the mechanism of MES differentiation may be of great benefit for the treatment of GBM. NF-κB signaling is critically important in GBM, and activation of NF-κB could induce MES transdifferentiation in GBM, which warrants additional research. NUDT21 is a newly discovered tumor-associated gene according to our current research. The exact roles of NUDT21 in cancer incidence have not been elucidated. Here, we report that NUDT21 expression was upregulated in human glioma tissues and that NUDT21 promoted glioma cell proliferation, likely through the NF-κB signaling pathway. Gene set enrichment analysis (GSEA), western blotting and RT-qPCR confirmed that NF-κB inhibitor zeta (NFKBIZ) was a downstream target affected by NUDT21 and that the MES identity genes in glioblastoma cells, CHI3L1 and FN1, were also differentially regulated. Our results suggest that NUDT21 is an upstream regulator of the NF-κB pathway and a potential molecular target for the MES subtype of GBM.